PENGARUH KUALITAS AUDIT, UKURAN PERUSAHAAN, KOMPLEKSITAS PERUSAHAAN DAN RISIKO PERUSAHAAN TERHADAP AUDIT FEE - Kezia Sibuea; Rizka Indri Arfianti (Jurnal Akuntansi, 2021)
Companies that hire an auditor to audit their financial statements are charged an audit fee. The audit fee is a payment given by the company to the auditor in exchange for his or her services. The purpose of this study is to discover if audit quality, firm size, complexity, and company risk all play a role in setting audit costs for financial statements. This study used a purposive sampling technique using a sample of 54 manufacturing businesses listed on the Indonesia Stock Exchange for the 2017-2019 period. Data analysis techniques used include the descriptive analysis test, classical assumption test, multiple regression analysis test, simultaneous test (f-test), and partial test (t-test). According to the findings of the study, audit quality, firm size, and firm complexity all have a significant positive impact on audit fees. While the firm risk variable is not proven to have an effect on audit fees. Keywords: Audit fee, Audit quality, Company size, Company complexity, Company risk. References: Agoes, S. (2017). Auditing: Petunjuk Praktis Pemeriksaan Akuntan Oleh Akuntan Publik. Jakarta: Salemba Empat. Ahmad, A. C., & Abidin, S. (2008). Audit Delay of Listed Companies: A Case of Malaysia. CCSE International Business Research., Vol. 1, No.4 October 2008, 32-39. Akram, Basuki, P., & Budiarto. (2017). Pengaruh Mekanisme Corporate Governance, Kualitas Audit, Ukuran Perusahaan dan Leverage Terhadap Integritas Laporan Keuangan. Vol.2, No.1, Oktober 2017, 95-120. Arens, A. A., Elder, R. J., Beasley, M. S., & Hogan, C. E. (2017). Auditing and Assurance Services: An Integrated Approach, Sixteenth Edition. Newyork: Pearson Prentice Hall. Ask, J., & Holm, M. L. (2013). Audit Fee Determinants in Different Ownership Structures. Uppsala University, 1-49. Awuy, V. P., Sayekti, Y., & Purnamawati, I. (2016). Pengaruh Pengungkapan Corporate Social Responsibility (CSR) Terhadap Earnings Response Coefficient (ERC). Jurnal Akuntansi dan Keuangan, 18, No.1, 15-26. Chandra, M. O. (2015). Pengaruh Good Corporate Governance, Karakteristik Perusahaan dan Ukuran KAP Terhadap. Jurnal Akuntansi Bisnis, Vol. 8, No. 26 Maret 2015, 174-194. Cooper, D. R., & Schindler, P. S. (2017). Metode Penelitian Bisnis (12 ed.). Jakarta: Salemba Empat. Cristansy, J., & Ardiati, A. Y. (2018). Pengaruh Kompleksitas Perusahaan, Ukuran Perusahaan dan Ukuran KAP Terhadap Audit fee Pada Perusahaan Manufaktur Yang Terdaftar di BEI Tahun 2012-2016. Modus Journal Vol. 30, No.2: 198-211 ISSN: 0852-1875, ISSN (Online): 2549 3787, 198-211. DeAngelo, L. E. (1981). Auditor Size and Audit Quality. Journal of Accounting and Economics Vol. 3 (1981), 183-199. Eisenhardt, K. M. (1989). Agency Theory: An Assessment and Review. Academy of Management Review, Vol.14, No. 1, 57-74. Gammal, W. E. (2012). Determinants of Audit Fees: Evidence from Lebanon. International Business Research, Vol. 5, No. 11: 2012, 136-145. Ghozali, I. (2018). Aplikasi Analisis Multivariate Dengan Program IBM SPSS 25. Semarang: Badan Penerbit Universitas Diponegoro. Hasan, M. A. (2017). Pengaruh Kompleksitas Audit, Profitabilitas Klien, Ukuran Perusahaan dan Ukuran Kantor Akuntan Publik Terhadap Audit Fee. Pekbis Jurnal, Vol. 9, No. 3, November 2017, 214-230. Huri, S., & Syofyan, E. (2019). Pengaruh Jenis Industri, Ukuran Perusahaan, Kompleksitas Perusahaan dan Profitabilitas Klien Terhadap Audit Fee. Jurnal Eksplorasi Akuntansi, Vol. 1, No. 3, 1096-1110. Retrieved from http://jea.ppj.unp.ac.id/index.php/jea/issue/view/9 Institut Akuntansi Publik Indonesia (IAPI). (2016). Undang-Undang Nomor 2 Tahun 2016 Tentang Penentuan Imbalan Jasa Audit Laporan Keuangan. http://iapi.or.id/uploads/content/95-PP-No-2-Tahun-2016- tentang-Penentuan-Imbalan-Jasa-Audit-Laporan-Keuangan.pdf ICAEW. (2005). Audit Quality: Agency Theory and The Role of Audit. Audit and Assurance Faculty. Immanuel, R., & Yuyetta, E. N. (2014). Analisis Faktor-Faktor Yang Mempengaruhi Penetapan Audit Fees. DIPONEGORO JOURNAL OF ACCOUNTING, Volume 3, Nomor 3, Tahun 2014, 1-12. Retrieved from http://ejournal-s1.undip.ac.id/index.php/accounting Indriastuti, M. (2012). Analisis Kualitas Auditor dan Corporate Governance Terhadap Manajemen Laba.Eksistansi (ISSN 2085-2401), Vol. IV, No. 2, Agustus 2012. Jensen, M. C., & Meckling, W. H. (1976). Theory Of The Firm: Managerial Behavior, Agency Costs And Ownership Structure. Journal of Financial Economics Vol. 3 (1976), 305-360. Julianto, I. A., Yadnyana, I., & Suputra, I. G. (2016). Pengaruh Audit Fee, Perencanaan Audit Dan Resiko Audit Terhadap Kualitas Audit Pada Kantor Akuntansi Publik di Bali. E-Jurnal Ekonomi dan Bisnis Universitas Udayana, Vol. 5, No. 12, 2016, ISSN: 2337-3067, 4029-4056. Keputusan BAPEPAM No. KEP-36/PM/2003, Tentang Kewajiban Penyampaian Laporan Keuangan Berkala. (2003). https://docplayer.info/30003274-Keputusan-ketua-badan-pengawas-pasar-modal-nomor-kep- 36-pm-2003-tentang-kewajiban-penyampaian-laporan-keuangan-berkala.html Nugrahani, N. R., & Sabeni, A. (2013). Faktor-Faktor yang Mempengaruhi Penetapan Fee audit Eksternal Pada Perusahaan Yang Terdaftar Di BEI. Diponegoro Journal of Accounting, Volume 2, Nomor 2, Tahun 2013, ISSN(Online): 2337-3806, 1-11. Pambudi, T. L., & Ghozali, I. (2013). Pengaruh Kepemilikan Perusahaan Dan Manajemen Laba Terhadap Tipe Auditor Dan Audit Fees Pada Perusahaan Manufaktur Di Bursa Efek Indonesia. Diponegoro Journal of Accounting, Volume 2, Nomor 1, Tahun 2013, 1-13. Pranama, R. S. (2019). Pengaruh Pelaporan Corporate Social Responsibility, Kualitas Auditor, Ukuran Perusahaan, Anak Perusahaan dan Resiko Perusahaan Terhadap Komitmen Audit Laporan Keuangan (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI 2015-2017). Universitas Islam Indonesia, Yogyakarta. Sanusi, M. A., & Purwanto, A. (2017). Analisis Faktor Yang Mempengaruhi Biaya Audit Eksternal, Diponegoro Journal of Accounting, Volume 6, Nomor 3, Tahun 2017, ISSN(Online): 2337-3806, 1-9. Selano, E. C., Tedjasuksmana, B., & Wardani, R. P. (2017). Faktor-Faktor Yang Mempengaruhi Kecenderungan Kecurangan Laporan Keuangan Pada Perusahaan Property, Real Estate and Building Yang Terdaftar di BEI Tahun 2013-2015. Jurnal Akuntansi Kontemporer (JAKO), Vol. 9, No. 2, Juli 2017, 162-182. Suharli, M., & Nurlaelah. (2008). Konsentrasi Auditor Dan Penetapan Fee audit: Investigasi Pada BUMN, JAAI, Volume 12, No. 2, Desember 2008, 133-148. Syafina, D. C. (2018, Oktober 8). Kasus SNP Finance dan Pertaruhan Rusaknya Reputasi Akuntan Publik. (Suhendra, Editor) Retrieved from tirto.id: https://tirto.id/kasus-snp-finance-dan-pertaruhan- rusaknya-reputasi-akuntan-publik-c4RT Triani, Y. O. (2016). Faktor-Faktor Yang Mempengaruhi Penetapan Fee audit Fees (Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia pada Tahun 2011-2013). Ulfasari, H. K., & Marsono. (2014). Determinan Fee audit Eksternal Dalam Konvergensi IFRS. Diponegoro Journal of Accounting, Volume 3, Nomor 2, Tahun 2014, ISSN(Online): 2337-3806, 1-11. Watkins, A. L., Hillison, W., & Morecroft, S. E. (2004). Audit Quality: A Synthesis of Theory And Empirical Evidence. Journal of Accounting Literature, Vol. 23, tahun 2004, ABI/INFORM Global, 153-193. Widiastari, P. A., & Yasa, G. W. (2018). Pengaruh Profitabilitas, Free Cash Flow, dan Ukuran Perusahaan pada Nilai Perusahaan. E-Jurnal Akuntansi Universitas Udayana, Vol. 23, No. 2, Mei 2018, ISSN: 2302-8556, 957-981. doi:https://doi.org/10.24843/EJA.2018.v23.i02.p06 Yulianti, N., Agustin, H., & Taqwa, S. (2019). Pengaruh Ukuran Perusahaan, Kompleksitas Audit, Risiko Perusahaan dan Ukuran KAP Terhadap Fee audit. Jurnal Eksplorasi Akuntansi, Vol. 1, No. 1, Seri B, Februari 2019, ISSN: 2656-3649 (Online), 217-235. Yulio, W. S. (2016). Pengaruh Konvergensi IFRS, Komite Audit Dan Kompleksitas Perusahaan Terhadap Fee audit. Jurnal Akuntansi Bisnis, Vol. 15, No. 29, 29 September 2016, 77-92.